MULTICULTURAL AND ETHNICITY HISTORY APPROACH TOWARDS NATIONAL INTEGRATION IN MALAYSIA - Seman, Ahmad Ali (Historia: Jurnal Pendidik dan Peneliti Sejarah, 2010)
Integration is a process to create national identity in a society which is differs in culture, social matter, location that live in a political unit. The concept of national integration is actually a broad concept. From sociological perspective, the process of understanding can be explained as integration, as in political integration resulted from the efforts in cooperating and uniting the parties that have followers with various ideological background. The national integration process happens as the result of the needs to strengthen the harmony and security for a sovereign country. Malaysia, however, has taken several concrete steps to bridge the diversity in ideology, politics, economy, and social matter, along with the efforts towards educational system. History education had been made as the main choice in Malaysia in order to realize the goal of teaching political value as well as its importance. History also plays a role in improving socialization and awareness towards politics within the young generation, as well as strengthening nationalism as an important element to build a good citizenship. History education should be able to foster national integration and national development. The awareness towards historical heritage is important to foster group identity that later may form the sense of belonging, love, empathy and loyalty. The development on history education in Malaysia shows that the subject of history has been made as a bridge in achieving the above goal (KPM, 2003) namely to foster the loyalty and identity as the citizen of Malaysia and as the member of the world society. Multicultural perspective is important to be delivered in history education so that every ethnic will be pround and respected. Multiculturality and diversity should be considered as a potential to foster diversity into national integration. History may also build an understanding and respect as well as explores other ethnic cultures as to find similarities that can be accepted nationally to build tolerant and to prevent clash among ethnics in Malaysia in the future time.